Positive and negative factors for the successful adoption of Public Private Partnership (ppp): evidence from Malaysia - Ismail, Suhaiza (IIUM Press, 2013)
This study aims to investigate the factors that atract and hinder the successful adoption of PPP in Malaysia. A questionnaire survey was used to elicit the perceptions of the public and private sectors concerning the positive and negative factors of PPP adoption in Malaysia. The 179 usable responses obtained were analysed using SPSS to rank the importance of the factors. The results show that the top five positive factors for adopting PPP in Malaysia are 'fasilitate creative and innovative approaches,' 'solve the problem of public sector budget constraints,' 'provide an integrated solution,; ;benefit to local economic development' and 'accelerate project development.' While the top factors for factors hindering the use of PPP the top factors include 'lengthy delays in negotiation,' 'lack of government guidelines and procedures on PPP,' 'higher chrge to the direct users,'lengthy delays because of political debate, and 'a great deal of management time spent in contract transaction.'